UJI AKTIVITAS ANTIOKSIDAN Syzygium polyanthum DAN Terminalia catappa L. SECARA IN VITRO DAN IN SILICO - Maulana, Luthfi Hidayat; Prastyono, Rizki Noor; Prayogi, Syaiful; Murniningsih, Erni; Alfarikhi, M. Zidan (Parapemikir : Jurnal Ilmiah Farmasi, 2023)
Reactive Oxygen Species (ROS) is a radical which is a by-product of metabolic processes. An imbalance between the number of free radicals and the amount of endogenous antioxidants can cause oxidative stress and cause problems for body cells that can cause various metabolic diseases or other degenerative diseases. Exogenous antioxidants can be chemical compounds resulting from synthesis or materials derived from nature that can inhibit the oxidation process. Phenol group compounds can be used as antioxidants. Salam plants (Syzygium polyanthum) and ketapang (Terminalia catappa L.) are rich in phenols. In vitro antioxidant testing using other methods such as DPPH (2,2-Diphenyl-1-Pikrylhidrazyl), in silico, molecular docking was carried out by targeting the heme oxygenase-1 (HO-1) protein to test antioxidant activity with analysis showing binding and strengthening evidence of impending chemical interactions. Based on in vitro testing, ketapang leaf extract has better antioxidant activity compared to bay leaf extract, with an IC50 value of 6.631 and the in silico results of the constituent compounds of ketapang leaves have the best docking value, namely compound 14 with a value of -88.18. Both of these test results reinforce each other